Grassroots and local initiatives versus the architect's design during China's reform and opening process - Qing-Ping Ma (Essays in Economic & Business History (EEBH), 2021)
China's rapid economic growth since 1978 has been mainly credited to the leadership of the Communist Party of China (CPC), especially Deng Xiaoping, in the official narratives. This article examines key events before and during China's reform and opening, and concludes that the enterprising spirit of ordinary Ch inese people and grassroots initiatives are the real driving forces of China's rapid growth. The main role of Deng and the CPC leadership was permissive to the grassroots initiatives. Deng Xiaoping's "Uphold Four Cardinal Principles" has shut the door for political reform and kept state control of key economic sectors.
Keywords: N15; N95; O53; 330; China miracle; household contract responsibility system; private enterprise; state owned enterprise; township and village enterprise